Hepatocellular carcinoma in patients with non-alcoholic steatohepatitis – epidemiology, risk factors, clinical implications and treatment - Straś, Wojciech; Małkowski, Piotr; Tronina, Olga (Clinical and Experimental Hepatology, 2020)
In recent years, rapid growth of incidence of metabolic syndrome, obesity and diabetes has been noted worldwide. Concurrent non-alcoholic steatohepatitis (NASH) has become a dominant factor of hepatic cirrhosis and hepatocellular carcinoma (HCC). The most important risk factors of transition from NASH to HCC are the degree of liver fibrosis, diabetes, obesity, age and male gender. Body mass index (BMI) reduction and increase of physical activity limit the risk of occurrence of HCC. Also, treatment of diabetes with metformin and application of statins have potential anticancer effects. Patients with HCC due to NASH should be treated in line with BCLC staging. Distant results of HCC therapy in the course of non-alcoholic fatty liver disease (NAFLD) are similar to the results of cancer of different aetiologies. However, patients with the metabolic syndrome are at high perioperative risk, and thus require accurate preparation, especially cardiological, in order to avoid that risk.